The impact of compensation upon urban village residents satisfaction with the land expropriation process: Empirical evidence from Hangzhou, China. Issue 3 (28th August 2019) - Chai, Ning; Stevens, Rob; Fang, Xiaozhen; Mao, Chun; Wang, Ding
Abstract : Purpose: The purpose of the paper is to investigate compensation and related welfare issues in the case of the expropriation of land for urban redevelopment in China. Design/methodology/approach: A mixed methods quantitative and qualitative approach was selected to undertake the research. This involved a wide ranging qualitative review of the academic and policy literature to explore the relevant arguments and issues, combined with a quantitative regression analysis of survey data collected from research subjects. Findings: The research identified the complex and changeable phenomena of urban village redevelopment in China, and the variable compensation arrangements used. The research found that monthly family income before land expropriation, monthly family expense before expropriation, the location of the housing expropriation and family unit size are important determinants for the property holders chosen methods of compensation. It also found that an increase in family size leads to a decreasing probability that the expropriated farmers choose the single monetary compensation relative to the alternative option of housing compensation. The degree of satisfaction with compensation, changes in monthly family income and expense are found to be significant determinants for changes in life satisfaction. Research limitations/implications: The research made the following four recommendations based upon the qualitative and quantitative analysis: that local governments should pay closer governance/ political attention to changes in the welfare of the farmers/ villagers whose property has been expropriated; that central and local government should aim to improve the compensation system for rural land and property expropriation, to make the compensation policy be perceived as fairer and more reasonable by citizens; that a broad National standard of compensation be used within a pragmatic locally focussed regime; that the Chinese Central, Provincial and Local governments can devise improved policy tools and make more effective policy interventions by learning from the experiences (both successes and failures) of other countries approaches to this topic. It also suggested that further research be undertaken investigating the multitude of local level policy experiments, as a way of developing better National compensation standards based upon those compensation standards that appear to be working – and have citizen support – at the local level. Originality/value: The literature review identified recent developments in Chinese urban studies and originally synthesised both recent and longstanding work on the issue of urban villages in China. The research also suggested changes to the National and Local legal and policy framework for compensation cases in urban redevelopment expropriation scenarios.